2014
DOI: 10.17221/70/2014-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new molecular marker C2-25 linked to the Fusarium oxysporum f.sp. radicis-lycopersici resistance Frl gene in tomato

Abstract: Fusarium oxysporum Schlecht. f.sp. radicis-lycopersici Jarvis & Schoemaker (FORL) is a saprophytic fungus, responsible for the fusarium crown and root rot disease in tomato (Solanum lycopersicum L.). This is one of the most destructive pathogens of this species. A new cleaved amplified polymorphic sequence (CAPS) marker C2-25 was developed for the detection of the dominant gene Frl, which confers tomato resistance to FORL. C2-25 was amplified from a conserved ortholog set II (COSII) sequence C2_At2g38025. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…9, as reported earlier (Vakalounakis et al 1997, Fazio et al 1999, Mutlu et al 2015, indicating that the FORL resistance in 'AV107-4' might have originated from the Frl of an S. peruvianum accession. However, the results on the genomic location of Frl were contradictory between recently published D r a f t studies and our study: by using an F 2 population, Staniaszek et al (2014) mapped the COSII marker C2_At2g38025 at 3 cM distal to Frl in line '3070'. The C2_At2g38025 was positioned at 45 cM of Chr.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…9, as reported earlier (Vakalounakis et al 1997, Fazio et al 1999, Mutlu et al 2015, indicating that the FORL resistance in 'AV107-4' might have originated from the Frl of an S. peruvianum accession. However, the results on the genomic location of Frl were contradictory between recently published D r a f t studies and our study: by using an F 2 population, Staniaszek et al (2014) mapped the COSII marker C2_At2g38025 at 3 cM distal to Frl in line '3070'. The C2_At2g38025 was positioned at 45 cM of Chr.…”
Section: Discussioncontrasting
confidence: 99%
“…9 and in locations linked to FORL resistance (Mutlu et al 2015). However, similar to the findings of Staniaszek et al (2014), our present results strongly suggested that FORL resistance in 'AV107-4' was closely linked to the PNU-D4 marker, which is in the vicinity of 6.0 Mb (50.0 cM of Chr. 9 on Tomato-EXPEN 2000 map) for which genetic recombination (crossing over) is severely suppressed.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We were unable to find any bacterial isolate that could control both the Fol R3 and Forl pathogens ( Table 1 ), thus rejecting our first hypothesis. To date, no resistance to Forl has been described in tomato ( Ates et al, 2019 ), and even though the Frl resistance gene that confers partial resistance to Forl was identified in 2001 ( Staniaszek et al, 2014 ), the nature of this gene is still unknown. It is possible that the antagonistic mechanisms required to inhibit growth of both pathogens could be very different, which would explain why we could not find a common isolate able to control both fungal tomato pathogens.…”
Section: Discussionmentioning
confidence: 99%